2021
DOI: 10.1093/ehjcr/ytab526
|View full text |Cite
|
Sign up to set email alerts
|

Hypoplastic coronary artery disease and hypertension in a child: a case report

Abstract: Background Hypoplastic coronary artery disease (HCAD) is an extremely rare disease associated with a risk of sudden cardiac death. It is rarely recognized in a live pediatric patient. Case summary We report a case of HCAD in a patient who first presented with vomiting and poor feeding, suggestive of acute heart failure due to cardiomyopathy or acute myocarditis in infancy. Hypertension and signs of ischemia became evident on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Eighty-eight studies were excluded due to discrepancies between their primary and secondary results compared to those of this review, or because they failed to meet the established criteria for good data extraction. Therefore, 39 articles [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ] were selected for this study ( n = 140,137) (including patients, images, and cadavers) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Eighty-eight studies were excluded due to discrepancies between their primary and secondary results compared to those of this review, or because they failed to meet the established criteria for good data extraction. Therefore, 39 articles [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ] were selected for this study ( n = 140,137) (including patients, images, and cadavers) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Prior investigations failed to establish a concrete correlation between the presence of HCAD and the development of hypertension. Nevertheless, among 17 documented pediatric cases, two exhibited hypertension, posited as a compensatory mechanism at preserving coronary perfusion [28]. At the same time, it is important to remember that hypertension stands as a primary precipitant in the development of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…The significant reduction in the luminal diameter and length of one or more main coronary arteries characterizes hypoplastic coronary artery disease (HCAD). 14 , 15 According to the Indian population study on the normal diameters of the left main coronary artery, the proximal left anterior descending artery, proximal right coronary artery, and proximal left circumflex artery are respectively 4.08±0.44mm, 3.27±0.23mm, 3.20± 0.37mm, 2.97±0.37 mm. 16 Most of HCAD cases are more frequently detected during autopsies than by in vivo coronary angiography.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent advanced studies on cases with HCAD, both congenital and acquired factors influence coronary artery flow. 14 , 15 The formation of the coronary arteries has been the subject of some research. It has been suggested that some genetic variables may be connected to HCAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation